Assessment and optimization of a natural coagulant (Musa paradisiaca) peels for domestic wastewater treatment - zaidi, Nur syamimi; Chin Ting, Won; Zhan Loh, Zhang; Burhanuddin Bahrodin, Muhammad; Azimatolakma Awang, Nik; Kadier, Abudukeremu (Environmental and Toxicology Management, 2022)
Sustainable wastewater treatment necessitates the application of natural and green material in the approach. Thus, selecting a natural coagulant in wastewater treatment is a crucial step to prevent secondary environmental pollution due to residual inorganic coagulant in treated effluent. Present study investigated the application of Musa paradisiaca (banana) peels in domestic wastewater treatment. From the experimental results, the banana peels were found to have a higher yield with lower moisture content compared to the other fruit wastes. The surface charge of the banana peels was +6.53 meq/g MLSS while the recorded protein composition was 0.248 mg/L. The scanning electron microscopy (SEM) showed that banana peels has rough and pore surfaces compared to the others fruit wastes. At optimum conditions of 50 mg/L dosages, pH 4, and 100 rpm of agitational speed, the maximum turbidity removal of up to 89.9% with initial turbidity of 76 NTU was obtained. The banana peel was also evidenced in efficiently removing COD and NH4-N from domestic wastewater up to 80.0% and 62.5%, respectively. Overall, the findings suggested that Musa paradisiaca (banana) peels is efficient and suitable to be applied as the natural coagulant in treating domestic wastewater.